2022
DOI: 10.1002/btpr.3240
|View full text |Cite
|
Sign up to set email alerts
|

A novel modified culture medium for enhancing redifferentiation of chondrocytes for cartilage tissue engineering applications

Abstract: The dedifferentiation of articular chondrocytes during in vitro expansion deteriorates the hyaline cartilage regeneration. Many approaches have been developed to enhance the redifferentiation of chondrocytes. In this study, a new and effective protocol to improve the redifferentiation of porcine chondrocytes in a pellet form was established. Pellets were initially treated in the modified culture media containing ternary mixtures, binary mixtures, or single reagents of sodium citrate (SCi), sodium chloride (SCh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 45 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…In this study, the viability of chondrocytes encapsulated in alginate microbeads was slightly reduced when the microbeads were incubated with the SCB treatment medium for 3 days. Our previous report demonstrated that the viability of chondrocyte pellet was negatively affected by SCB in a dose‐dependent manner 30 . However, all the tested SCB treatment medium exhibited no cytotoxicity (over 80% viability) due to the low SCB concentrations used in this study.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…In this study, the viability of chondrocytes encapsulated in alginate microbeads was slightly reduced when the microbeads were incubated with the SCB treatment medium for 3 days. Our previous report demonstrated that the viability of chondrocyte pellet was negatively affected by SCB in a dose‐dependent manner 30 . However, all the tested SCB treatment medium exhibited no cytotoxicity (over 80% viability) due to the low SCB concentrations used in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Our previous report demonstrated that the viability of chondrocyte pellet was negatively affected by SCB in a dose-dependent manner. 30 However, all the tested SCB treatment medium exhibited no cytotoxicity (over 80% viability) due to the low SCB concentrations used in this study. Members of the transforming growth factor-β (TGF-β) superfamily are well known for regulating chondrogenesis 34 and inducing cell proliferation.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations